2020
DOI: 10.1155/2020/5915173
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Numerical Calculation Method for Antiloosening Performance of Screwed Joints under Complex Working Conditions

Abstract: This study aimed at addressing the difficulties entailed in accurately determining the working loads of screwed joints (SJs) by establishing mechanical models and verifying the accuracy of the numerical calculation model of antiloosening performance under complex working conditions. First, considering the slip state of the interface and the stress state of the thread surface, a corresponding mechanical model was established to investigate the quantitative model of the interaction amongst structural parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, another study also suggested the suppression or hindrance of loosening through preload and increased friction coefficients and reducing the clamping field's length and tight tolerance [10]. Mo also emphasized the parameters influencing the relaxation, such as the effect of transverse and axial load, bending moment, and friction coefficient on anti-loosening performance [21]. Furthermore, previous research conducted using another STC model has shown that looseness was initiated by vibration [22][23][24].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, another study also suggested the suppression or hindrance of loosening through preload and increased friction coefficients and reducing the clamping field's length and tight tolerance [10]. Mo also emphasized the parameters influencing the relaxation, such as the effect of transverse and axial load, bending moment, and friction coefficient on anti-loosening performance [21]. Furthermore, previous research conducted using another STC model has shown that looseness was initiated by vibration [22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…The process involved preparing a jig with sturdy construction and resistance to vibration, followed by the use of a strain gauge for data acquisition. The strain gauge was used to directly monitor the changes in strain and tension when appropriately placed, after which the data obtained were processed and analyzed [21,22,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Through theoretical research and experimental verification (Nassar and Xianjie, 2007;Nassar and Yang, 2008), obtained equations that can predict the torque and clamping force between threads and bearings and calculation equations between thread friction, pitch, and torque components. Mo et al (2020) proposed a numerical calculation model for thread anti-loosening and verified its reliability through experiments. The research results show that the load has a more significant impact on the anti-loosening performance.…”
mentioning
confidence: 92%